Association of IFNL3 and IFNL4 polymorphisms with liver‐related mortality in a multiracial cohort of HIV/HCV‐coinfected women. Issue 12 (26th June 2015) - Sarkar, M.; Aouzierat, B.; Bacchetti, P.; Prokunina‐Olsson, L.; French, A.; Seaberg, E.; O'Brien, T. R.; Kuniholm, M. H.; Minkoff, H.; Plankey, M.; Strickler, H. D.; Peters, M. G.; et al.
Summary African Americans coinfected with HIV and hepatitis C virus (HCV) have lower liver‐related mortality than Caucasians and Hispanics. While genetic polymorphisms near the IFNL3 and IFNL4 genes explain a significant fraction of racial differences in several HCV‐related outcomes, the impact of these variants on liver‐related mortality has not been investigated. We conducted a cohort study of HIV/HCV‐coinfected women followed in the multicentre, NIH‐funded Women's Interagency HIV Study (WIHS) to investigate whether 10 polymorphisms spanning the IFN‐λ region were associated with liver‐related mortality by dominant, recessive or additive genetic models. We also considered whether these polymorphisms contributed to previously reported differences in liver‐related death by race/ethnicity (ascertained by self‐report and ancestry informative markers). Among 794 coinfected women, there were 471 deaths including 55 liver‐related deaths during up to 18 years of follow‐up. On adjusted analysis, rs12980275 GG genotype compared to AG+AA hazards ratios [(HR) 0.36, 95% CI 0.14–0.90, P = 0.029] and rs8109886 AA genotype compared to CC+AC (HR 0.67, 95% CI 0.45–0.99, P = 0.047) were most strongly associated with liver‐related death although these associations were no longer significant after adjusting for race/ethnicity (HR 0.41, 95% CI 0.16–1.04, P = 0.060 and HR 0.78, 95% CI 0.51–1.19, P = 0.25, respectively). African American women had persistently lower liver‐related death independent of IFN‐λ variants (HRs ≤ 0.44, P values ≤ 0.04). The lower risk of death among African American HIV/HCV‐coinfected women is not explained by genetic variation in the IFN‐λ region suggesting, that other genetic, behavioural and/or environmental factors may contribute to racial/ethnic differences in liver‐related mortality.